2009
DOI: 10.1063/1.3243287
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a gas discharge plasma source for extreme ultraviolet interference lithography at a wavelength of 11 nm

Abstract: In this work, we report about the optimization of the spectral emission characteristic of a gas discharge plasma source for high-resolution extreme ultraviolet (EUV) interference lithography based on achromatic Talbot self-imaging. The working parameters of the source are optimized to achieve a required narrowband emission spectrum and to fulfill the necessary coherence and intensity requirements. The intense 4f-4d transitions around 11 nm in a highly ionized (Xe8+-Xe12+) xenon plasma are chosen to provide the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…For our measurements, we employed a gas-discharge plasma EUV light source developed at the Fraunhofer Institute for Laser Technology [18][19][20] and specifically designed for water window operation (280 eV-530 eV). In our experiments, the source parameters were 3.5 kV discharge voltage, 2 μF total capacity and 20 Hz pulse repetition rate.…”
Section: Characterization Of the Plasma Emission Spectrum Behindmentioning
confidence: 99%
See 1 more Smart Citation
“…For our measurements, we employed a gas-discharge plasma EUV light source developed at the Fraunhofer Institute for Laser Technology [18][19][20] and specifically designed for water window operation (280 eV-530 eV). In our experiments, the source parameters were 3.5 kV discharge voltage, 2 μF total capacity and 20 Hz pulse repetition rate.…”
Section: Characterization Of the Plasma Emission Spectrum Behindmentioning
confidence: 99%
“…[18][19][20] The multiply ionized atoms, in our case oxygen and nitrogen ions, emit narrowbandwidth spectral lines ( E/E = 10 −3 −10 −5 , where E is the photon energy) in the photon energy range between vacuum ultraviolet and soft X-rays. We optimized the EUV light source for operation above 50 eV photon energy.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the peak at 110 Å becomes dominant when a buffer gas is added to the plasma. 25 While only Xe XI is important at 135 Å , many higher stages of xenon strongly emit in the UTA.…”
Section: A Time Integrated Spectramentioning
confidence: 99%
“…Хотя степень разбавления опре-деляется по давлениям газов перед соплом и соотношение атомар-ных концентраций в потоке точно неизвестно, полученный эффект очевиден и требует объяснения. Идея использования смеси Ar+Xe была предложена впервые в работе [13] для источника EUV-излучения на основе электродного плазменного фокуса. По мнению ее авторов, добавка Ar должна усиливать излучение Xe на длине волны λ = 11.2 nm и подавлять излучение с λ = 13.5 nm из-за специфической эволюции оптической толщины плазмы при разбавлении.…”
Section: поступило в редакцию 7 июля 2017 гunclassified